Penerapan Pendekatan Teaching At The Right Level (TaRL) Pada Mata Pelajaran Bahasa Indonesia Kelas VIII di SMP Negeri 8 Palembang - Hanindiya, Nur Azmi; Agustina, Juaidah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to explain the application of the Teaching at the Right Level (TaRL) approach in Indonesian language subjects in class VIII.5 at SMP Negeri 8 Palembang. This research is classified as qualitative descriptive research. Data sources used in this research include the learning process, information from the Indonesian language teacher at SMP Negeri 8 Palembang, teaching modules, and field notes about the learning process using the Teaching at the Right Level (TaRL) approach. Data collection techniques include observation, interviews and documentation analysis. The results of this research show that implementing learning using the Teaching at the Right Level approach is in line with the stages of the Teaching at the Right Level (TaRL) approach, namely classifying students' learning needs, planning and implementing learning, and reflecting and reproducing the learning process.